Impacts of land use and socioeconomic patterns on urban heat Island. Issue 11 (3rd June 2017) - Tang, Junmei; Di, Liping; Xiao, Jingfeng; Lu, Dengsheng; Zhou, Yuyu
ABSTRACT: Intensive land surface change and human activities induced by rapid urbanization are the major causes of the urban heat island (UHI) phenomenon. In this article, we examined the spatial variability of UHI and its relationships with land use and socioeconomic patterns in the Baltimore–DC metropolitan area. Census data, road network as well the digital elevation model (DEM) and average water surface percentage were selected to analyse the correlation between spatial patterns of UHI and socioeconomic factors. The impervious surface (coefficient of determination R 2  = 0.89) and normalized difference vegetation index ( R 2  = 0.81) were the two most important landscape factors, and population density ( R 2  = 0.57) was the most influential socioeconomic variable in contributing to the UHI intensity. Generally, the socioeconomic variables had smaller influence on the UHI intensity than the landscape variables. Based on the patch analysis, most of the socioeconomic variables influenced the UHI intensity indirectly through changing the physical environment (e.g. impervious surface or forest cover). The selected landscape and socioeconomic variables, except impervious surface percentage, demonstrated third-order polynomial correlation with the UHI intensity. The higher correlations were found within certain ranges such as forest percentage from 0% to 30% and population density from 0 to 5000 km –2 . This research provides a case study to understand the urban land surface, vegetation, and microclimate for urban management and planning.